Sharia Compliance with DSN-MUI Fatwa No.107/DSN-MUI/X/2016 Concerning Guidelines for Organizing Hospitals Based on Sharia Principles (Case Study at RSUD Brigjend H Hasan Basry Kandangan and Sultan Agung Islamic Hospital Banjarbaru) - Novia Indriani; Parman Komarudin; Umi Hani; Muhammad Hendri Yanova (NUKHBATUL 'ULUM: Jurnal Bidang Kajian Islam, 2024)
South Kalimantan has two hospitals based on sharia principles, namely RSUD Kandangan and Sultan Agung Islamic Hospital Banjarbaru which DSN-MUI has also recognized with a sharia certificate. The background of this research analyzes Sharia Compliance with DSN-MUI Fatwa No.107/DSN-MUI/X/2016 concerning Guidelines for the Implementation of Hospitals Based on Sharia Principles with the focus of Case Studies at RSUD Kandangan and Sultan Agung Islamic Hospital Banjarbaru. This study aims to examine the practice of organizing hospitals based on Sharia principles at RSUD Kandangan and Sultan Agung Banjarbaru Islamic Hospital. The suitability of hospital organization practices based on sharia principles at RSUD Kandangan and Sultan Agung Banjarbaru Islamic Hospital with DSN-MUI Fatwa No.107/DSN-MUI/X/2016. This research methodology uses descriptive qualitative research, with data sources derived from observation, interviews, and documentation. The research objects in this study are RSUD Kandangan and Sultan Agung Islamic Hospital Banjarbaru. The results of the study indicate that the practice of organizing hospitals based on Sharia principles in the two hospitals has been fully implemented even though it is still less than optimal in terms of ikhtilat and providing Islamic educational materials. The suitability of the practice of organizing hospitals based on Sharia principles at RSUD Kandangan and Sultan Agung Islamic Hospital Banjarbaru with DSN-MUI Fatwa No.107/DSN-MUI/X/2016 has also been in accordance as a whole so that the sharia certificate given by DSN-MUI is indeed appropriate to be given to the two hospitals.